Rancang Bangun Sistem Informasi Penjualan Kebutuhan Komputer Berbasis Web Pada Ruko Bantenbiz Komputer Menggunakan Metode Waterfall - Ramdan, Fahru (Jurnal Ilmu Komputer, 2025)
Ruko Bantenbiz Komputer is a business engaged in the sale of computer-related needs, including hardware, accessories, and other equipment. The sales process is still conducted manually, leading to several issues such as difficulties in managing transaction data, delayed services, and limited market reach. To address these problems, a web-based sales information system was designed and developed using the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The system was built using PHP Native as the programming language, Dreamweaver as the Integrated Development Environment (IDE), and MySQL as the database. With this system, the business owner can manage sales and inventory more efficiently, accelerate transaction processes, and provide easier access for customers to view product information and make online purchases. This system is expected to improve operational effectiveness and expand the market reach of Ruko Bantenbiz Komputer.